2007
DOI: 10.1002/pssc.200675839
|View full text |Cite
|
Sign up to set email alerts
|

Positron microscopic analysis of crack failure in stainless steels

Abstract: Employing a focused positron beam with a lateral resolution of approximately 30 µm, we performed two dimensional scanning studies of stainless steels with stress corrosion cracking (SCC). A stainless steel with fatigued crack was also measured for comparison. Results suggest a quite unique failure mechanism for the specimen with SCC. In contrast to normal crack propagation effect associated with vacancies and dislocations, smaller Doppler broadening line shape (S) parameters were observed around the SCC crack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…On the test bench equipped with the SEM magnetic lens, we have performed the formation of positron microbeam and evaluate the properties of this beam [9]. It was confirmed that positron beam was converged to ~80 µm when the source diameter was 4 mm.…”
Section: Beam Transportation and Microbeam Formationmentioning
confidence: 85%
See 1 more Smart Citation
“…On the test bench equipped with the SEM magnetic lens, we have performed the formation of positron microbeam and evaluate the properties of this beam [9]. It was confirmed that positron beam was converged to ~80 µm when the source diameter was 4 mm.…”
Section: Beam Transportation and Microbeam Formationmentioning
confidence: 85%
“…To obtain such positron microbeam, a well-focused and monoenergetic positron beam and an objective lens, which is commonly used in the electron microscopy, are required. We have attempted to form the positron microbeam using a high brightness positron beam for the positron diffraction experiment [8,9]. The beam diameter is ~80 µm and counting rate is ~50 cps, which is not enough for the detail two-dimensional scan of samples.…”
mentioning
confidence: 99%
“…To obtain such positron microbeam, it is necessary to use objective lenses, which are commonly used in the electron microscopy. We also attempted to form the positron microbeam using a positron beam for the positron diffraction experiment and a SEM optics [6][7][8]. The initial beam diameter (4 mm) was reduced to 80 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning positron microscopes (SPM) have been developed to apply PAS to very small samples or samples with small features of interest [3][4][5][6][7]. Slow positron beams of SPMs focus on samples where the beam spot size is less than a few tens of µm.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of such a SPM is that it can obtain two or three dimensional PAS images using the scanning lateral injection position (xy) and the implantation depth (z) of the focused beams, which allow the defect distributions to be visually evaluated. The AIST microbeam system [8] uses an electron linear accelerator (LINAC) to produce positrons [9,10], and consequently, its beam intensity (10 6 e + /s) is 10-100 times higher than those of the other SPMs [3][4][5][6], which use radioisotopes as the positron source. Therefore, the AIST microbeam system can obtain PAS images within a reasonable time (~10 3 pixels/hour) [11] and hence, SPM may be a practical tool.…”
Section: Introductionmentioning
confidence: 99%